2003
DOI: 10.1136/bmj.326.7392.740
|View full text |Cite
|
Sign up to set email alerts
|

Teaching as therapy: cross sectional and qualitative evaluation of patients' experiences of undergraduate psychiatry teaching in the community

Abstract: Objective To explore the impact of participating in undergraduate teaching in general practice for patients with common mental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 18 publications
4
63
0
Order By: Relevance
“…This supported earlier research that suggested the act of providing education to medical students resulted in consumer empowerment, increased self-esteem, development of new insights, and an improved understanding of the doctorpatient relationship. 46 The formation of an educational partnership, therefore, may have ongoing benefits for both groups. Although the results of this qualitative research cannot be generalized to all groups of consumers, pharmacists, and pharmacy students, this case study suggests that utilizing consumer educators in pharmacy education is a promising area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…This supported earlier research that suggested the act of providing education to medical students resulted in consumer empowerment, increased self-esteem, development of new insights, and an improved understanding of the doctorpatient relationship. 46 The formation of an educational partnership, therefore, may have ongoing benefits for both groups. Although the results of this qualitative research cannot be generalized to all groups of consumers, pharmacists, and pharmacy students, this case study suggests that utilizing consumer educators in pharmacy education is a promising area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…It also keeps tutors in touch with current issues relating to mental health service delivery, which is very relevant given the findings of the report by Owen et al (2005) in relation to the clinical activity of lecturers. For the service users and carers who take on these training roles, benefits that have been described include the development of a more balanced doctor-patient relationship, a better appreciation of professional perspectives (Walters et al, 2003) and the enhancement of recovery linked with improved selfesteem because of having a training role that is valued (Masters et al, 2002).…”
Section: Involving Carers and Service Users In The Training Of Psychimentioning
confidence: 99%
“…There were also some negative impacts reported from both the Gecht (2000) and Walters et al (2003) studies. Gecht (2000) found that service users with chronic progressive conditions had an increased awareness of the progression of their disease and its impact on their lives.…”
Section: Literature Reviewmentioning
confidence: 81%
“…Stacey and Spencer (1999) reported that patients involved in training felt that they had learnt more about themselves and that it had helped them to talk about their illness. Similarly, Walters et al (2003) found that patients reported another positive outcome for them was the development of a coherent illness narrative.…”
Section: Literature Reviewmentioning
confidence: 95%